Efficacy Of First Time Furosemide Use In Thoroughbred Racehorses In Brazil - De Mello Costa, Maria Fernanda; Pereira, Juliana N.P.; Anderson, Garry A. (Revista de Saúde, 2018)
Racehorses are commonly affected by a condition known as Exercise Induced Pulmonary Haemorrhage (EIPH) which consists of rupture of alveolar membranes and extravasation of blood into the airways. EIPH is considered to negatively affect racehorse performance and there is no current treatment. In order to reduce the amount of bleeding the diuretic furosemide has been used prior to exercise and competition in some racing jurisdictions. Efficacy of furosemide in reducing EIPH is documented in this research through endoscopic observation of the airways of horses positive for EIPH in two consecutive races.